2017
DOI: 10.1371/journal.pone.0175877
|View full text |Cite
|
Sign up to set email alerts
|

A concept for optimizing avalanche rescue strategies using a Monte Carlo simulation approach

Abstract: Recent technical and strategical developments have increased the survival chances for avalanche victims. Still hundreds of people, primarily recreationists, get caught and buried by snow avalanches every year. About 100 die each year in the European Alps–and many more worldwide. Refining concepts for avalanche rescue means to optimize the procedures such that the survival chances are maximized in order to save the greatest possible number of lives. Avalanche rescue includes several parameters related to terrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Finally, in accidents involving multiple casualties (32%) or multiple CA patients (5%), complex medical triage skills are required to allocate the available human, material, and transport resources to those patients with the greatest chance of survival. [ 38 , 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in accidents involving multiple casualties (32%) or multiple CA patients (5%), complex medical triage skills are required to allocate the available human, material, and transport resources to those patients with the greatest chance of survival. [ 38 , 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…There are evidence-based search and rescue tools, such as AvaLife, that also include medical treatment protocols, striving for the greatest good for the greatest number in avalanche accidents with multiple burials and limited resources. 133 Other protocols have also been developed. 54 AvaLife contains a search and excavate module (Figures 3 and 4) as well as medical modules.…”
Section: Professional Rescuementioning
confidence: 99%
“…The fact that electronic devices compromise AT function is more pronounced in receiving mode than in transmitting mode is known and has been previously reported. 20 Our study revealed that even off-state heated gloves can interfere with AT function depending on the brand. This should be investigated more in detail in further studies.…”
Section: Discussionmentioning
confidence: 69%